Metal Allergy From Dermatitis to Implant and Device Failure (Springer International Publishing, 2018)
This volume has been compiled in response to the ongoing revolution in our understanding of metal contact allergy, and the ensuing challenge this has created for clinicians and others to synthesize large amounts of sometimes contradictory data. It opens by providing a comprehensive overview of the use and regulation of metals in our society, metal properties, and available testing methodologies. Common and uncommon metal allergens and sources of exposure are then reviewed in depth, and detailed sections are devoted to hypersensitivity to metal implants (which may be associated with device failure and/or dermatitis), metal allergy in select patient populations, and less frequently encountered manifestations of metal allergy. The prevalence of metal allergy in the general population is high: up to 17% of people are allergic to nickel, and 1-3% to cobalt and chromium. Environmental sources of metal exposure include jewelry, clothing, electronic devices, coins, leather, diet, and occupational exposure. As metals are ubiquitous, this book will be an indispensable reference text for a wide range of clinicians and investigators, meeting the needs of all who are interested in metal allergy and its diagnosis and management. .